COVID-19 surveillance in youth soccer during small group training: A safe return to sports activity - Drezner, J. A.; Drezner, S. M.; Magner, K. N.; Ayala, J. T. (Sports Health: A Multidisciplinary Approach, 2021)
The objective of this study was to monitor the prevelance of new infections within the Seattle United youth soccer club during small group, physically distanced training with comparison to the prevalence of infections within King County in the same time period.